2017
DOI: 10.13189/ujer.2017.050612
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Religious Beliefs about the Origin of Life and Life after Death: Validation of a Scale

Abstract: The variety of explanations to questions about the origin of life, life after death or about the role itself of being in the world are built on the rational reflection that integrates the ideology of human beings as well as less rational practices and more emotional ones than in the whole nourish what has been called "beliefs". Therefore, the aim of this study was to construct an instrument to measure beliefs about the origin of life and life after death. A scale with a Likert 5-point response type was made up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…We also found that catholics, evangelicals, agnostics, and atheists were less afraid of COVID-19. In this sense, it is worth noting that some religions, such as Christianity, have very dogmatic views, which associate life after death with the moral actions of human beings and the going of the soul to a place of reward or punishment [25]. A study carried out on anxiety in the face of death, concern about the time and fear associated with suffering from an illness, established that having religious beliefs and thinking about life after death generated greater anxiety [26].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that catholics, evangelicals, agnostics, and atheists were less afraid of COVID-19. In this sense, it is worth noting that some religions, such as Christianity, have very dogmatic views, which associate life after death with the moral actions of human beings and the going of the soul to a place of reward or punishment [25]. A study carried out on anxiety in the face of death, concern about the time and fear associated with suffering from an illness, established that having religious beliefs and thinking about life after death generated greater anxiety [26].…”
Section: Discussionmentioning
confidence: 99%
“…Mandalika University of Education is a university with diverse student characteristics, both in terms of religion and culture. There are several definitions of religious belief, which one that religious belief is related to the function of religious belief in life (Bautista, Escobar, & Miranda, 2017), that religious belief is related to the function of religious beliefs in life, but in the controversy between evolution and religion, acceptance and understanding of evolution is influenced by several factors, such as knowledge about evolution itself and religious beliefs (Arthur, 2013). However, several studies have shown that religious belief is related to religious practices, and only educational background is positively correlated with knowledge (Torkar & Sorgo, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Pemahaman mengenai penciptaan alam semesta merupakan studi dari kosmologi yang menjadi bagian di dalam cabang filsafat metafisika (Alcalde, 2019). Kosmologi atau studi tentang penciptaan telah banyak dijelaskan di dalam pandangan sains, agama, dan filsafat dengan berlandaskan keyakinan terhadap suatu pengetahuan (Bautista et al, 2017). Perbedaan keyakinan pengetahuan yang dimiliki setiap orang menunjukkan adanya posisi filosofis yang beragam dalam memahami kosmologi.…”
Section: Pemahaman Filosofis Siswa Mengenai Penciptaan Alam Semestaunclassified
“…Keyakinan tersebut juga dikenal sebagai keyakinan epistemologi (Knight, 2008). Berdasarkan ketiga teori tersebut dapat disimpulkan bahwa kosmologi merupakan bagian dari cabang filsafat metafisika yang berfokus pada pemahaman penciptaan alam semesta dan dibentuk secara filosofis dari keyakinan terhadap suatu pengetahuan (Alcalde, 2019;Bautista et al, 2017;Knight, 2008).…”
Section: Pemahaman Filosofis Siswa Mengenai Penciptaan Alam Semestaunclassified